If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5a + 7 = -23 Reorder the terms: 7 + 5a = -23 Solving 7 + 5a = -23 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + 5a = -23 + -7 Combine like terms: 7 + -7 = 0 0 + 5a = -23 + -7 5a = -23 + -7 Combine like terms: -23 + -7 = -30 5a = -30 Divide each side by '5'. a = -6 Simplifying a = -6
| 3(-x+2)+x-1=-x-3 | | 5t-6w=11 | | -5x+1=-10 | | 32k=2000 | | -33=-15+-12 | | 3x+20+4x+5=8x+15 | | 32=2000 | | 3(2x-5)+4(x-2)=12 | | 5(3x+5)=17+12 | | 3x^2=2x+21 | | 53=16x-3 | | x+38=86-3x | | 55=3x+2+13x-3 | | 14=7p-9p | | 11x=-44 | | 16z+4x=y | | 4x^2+6=26 | | 52[72]= | | 0.5[2x+8]=x-4 | | 2x+b=c | | -6+3x=6 | | 3x^2-12x+45=0 | | x*2-25y*2=0 | | 7x^2+6x+1=0 | | 14x+1=89+5x-7 | | x^2+12x-27=0 | | 3x-5+150+4x-10+5x-23+150+127+4x+15+100=1080 | | -7(x-2)-2(-5x-9)=2(x+4)+9 | | 2-8x=22 | | -13k=52 | | 6x-15+25=75 | | 4(x-5)-(-4x-6)=7x |